CHEMICAL CONSTITUENT DETECTION AND OXYTOXIC EFFECT OF INSOLUBLE ETHANOLIC FRACTION OF INFUSION OF Kaempferia angustifolia Roscue LEAVES ON ISOLATED UTERUS OF GUINEA PIGS - Pramono S.; Sumastuti R. (Indonesian Journal of Pharmacy, 2003)
To establish the scientific base on the use of Kaempferia angustifolia leaves as Indonesian post partus traditional drug, an experiment was done on isolated uterus guinea pigs. The infusion of Kaempferia angustifolia leaves was evaporated and the residu was then extracted with ethanol. The ethanolic fraction and the insoluble fraction were tested on isolated uterus guinea pig after addition of 1 ml of 10 IU/ml oxytocin. The active fraction was then dissolved in distlled water in order temterature. The chemical constituents of the active fraction were detected by thin layer chromatographic method. The results showed that the insoluble ethanolic fraction of the infusion increased significantly the contraction of uterus after the addition of oxytocin (p<00.5). Further more, the water soluble fraction and the residue of the active fraction had also similar activities.Keywords : Kaempferia angustifolia, oxytoxic effect, flavonoids, tanin, pectin